Traveling Man: The Journey of Ibn Battuta, 1325-1354 - Rumford, James (New York Houghton Mifflin Company, 2001)
Ibn Battuta was the traveler of his age--the 14th century in a time before Columbus, when many believed the world to be flat. Battuta journeyed from Morocco to China, from the steppes of Russia to the shores of Tanzania, some 75,000 miles in all.
Keywords: Ibn Battuta, 1304-1377.; Travelers; Voyages and travels